Developing a General Methodology and Construct a Driving Cycle with an Economic Performance Evaluation for Basrah City - S. Najem, Haider; A. Jawad, Qahtan; K. Ali, Abdulbaki; S. Munahi, Basil (International Journal of Engineering and Technology, 2018)
In this paper, a statistical method is employed to develop a driving cycle for Basrah city and to find out the factor score and the Euclidean distance analysis by the Statistical Package for the Social Sciences (SPSS). A simple electronic system is built to construct the driving cycle, the system considered a microcontroller and a GPS sensor connected to a PC through a simple C++ code. The development of the proposed driving cycle represents the first model driving cycle in the city of Basra. The advisor software package is used to investigate the economic performance of the internal combustion engine based on HC, CO, and NOx exhaust emissions. It was found that the obtained driving cycle is significantly different than the other driving cycles in terms of exhaust emissions and fuel consumption and within the expected range of emissions. The developed driving cycle model obtained is a representative delicate estimation of the exhaust emissions and fuel consumption, and will be utilized for future work to obtain a good performance of the hybrid electric vehicles.Â Â